Literature Review: Exploration of Natural Compounds for the Development of SARS-CoV2 Antiviruses through Docking-ADMET - Annisa, Hilma Tri; Weguna, Asti Awaliyah; Amin, Saeful (Jurnal Ilmu Medis Indonesia, 2026)
Purpose: This study aimed to investigate the antiviral potential of natural compounds against SARS-CoV-2 using an in-silico approach. The objective was to identify bioactive molecules from medicinal plants that effectively interact with viral target proteins and exhibit favorable pharmacokinetic and toxicity profiles. Methodology/Approach: A systematic literature review was conducted on publications from 2020 to 2025 obtained from PubMed, ScienceDirect, and Google Scholar. Studies applying molecular docking and ADMET prediction targeting key SARS-CoV-2 proteins–namely, Mpro, PLpro, RdRp, and TMPRSS2–were selected. Docking simulations were performed using AutoDock Vina, AutoDockTools, and PyRx, and ADMET parameters were analyzed using SwissADME, pkCSM, admetSAR, and ProTox. Results/Findings: Several compounds, including ginsenoside Rg2, azadirachtin A, Epigallocatechin Gallate (EGCG), curcumin, betulinic acid, and epicatechin-3-O-gallate, showed high binding affinities (-8. to-10. kcal/mol) and favorable pharmacokinetic and safety profiles, suggesting strong antiviral potential. Limitations: This study is limited to computational predictions without experimental validation. Consequently, the biological efficacy of the compounds remains theoretical and requires further confirmation. Contributions: This study integrates molecular docking and ADMET analysis to provide a comprehensive understanding of natural compounds as antiviral agents. It contributes to the development of safe, plant-based therapeutics and supports future in vitro and in vivo research. Conclusions: The findings confirm that the selected natural compounds possess promising inhibitory activity and acceptable safety against SARS-CoV-2. Validation through experimental and clinical studies is necessary to establish their pharmacological potential.